Exploring the Aesthetic of Empfindsamer Stil: A Case Study on Carl Philipp Emanuel Bach's Keyboard Sonata in A Major, Wq55 No.4’s Second Movement - Xiao, Jing (Transactions on Social Science, Education and Humanities Research, 2024)
This paper aims to analyze Carl Philipp Emanuel Bach's Keyboard Sonata in A Major, Wq55 No. 4’s second movement from different aspects to appreciate the charm of the Empfindsamer Stil. The analysis is from various aspects, such as harmonies, dynamics, ornamentation, and dramatic expressiveness in the sonata. In addition, this research will gain a deeper understanding of the aesthetic of this musical style and its significance in the development of Western classical music.